Higher Education Management Strategy In Preventing Drug Abuse In Asahan Regency - Abidin, Zainal; Aswan, Aswan; Wibowo, Kenny Agusto Arie (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this study is to analyze how the Higher Education Management Strategy in Preventing Drug Abuse in Asahan Regency The type of research in this study uses qualitative research, with a phenomenological approach. This research took place at private campuses/universities throughout Asahan Regency. Data collection techniques used interviews, field observations and documentation studies. Data processing and analysis techniques used data reduction, data presentation and drawing conclusions. The results of the study found that the management of higher education institutions towards preventing drug abuse in Asahan Regency, namely the need for active participation and participation in implementing drug abuse prevention activities carried out on campus, reporting all forms of possession, distribution or drug abuse that occur on campus, actively participating in training, seminars, workshops on preventing drug abuse both carried out by the campus and outside the campus, establishing good communication with peers and other campus residents (Rector, Dean, Head of College, Lecturers, parents, and campus security officers), and things that students can do to play a role in this industrial era and take steps and places as the driving force of this country is to develop critical thinking patterns and not be easily eroded by negative influences.